Doing qualitative analysis in psychology - Hayes, Nicky (Psychology Press, 1997)
In recent years, qualitative analysis has become accpeted as part of modern psychology. Concern about the limitations of conventional laboratory-based research combine with a growing interest in real world issues to produce an awareness of the rich potential of qualititative analysis. Virtualy all psychology students underatake practical work as part of their courses. More and more of them are seeking to conduct research which includes qualitative analysis. Too often, though, students lack awareness of the range and diversity of qualitative approaches. Qualitative analysis can take many different forms, and can use any different sources of data. At one end of the spectrum, this diversity provides the eclectic psychologists with a rich anaytical "tool-box". For those at the other end qualitative analysis is an integral part of a full theoretical critique of positivistic methodologies in psychology. This text provides examples of how different psychologists have used qualitative analysis in research. Each chapter is based around a real piece of research, and the researcher discusses exactly how they went about conducting the analysis. The text covers a wide range of theoretical and methodological approaches to qualitative analysis, and should be of interest to research psychologists as well as to students.